2020
DOI: 10.1002/agj2.20087
|View full text |Cite
|
Sign up to set email alerts
|

Silicon enhances yield and nitrogen use efficiency of tropical low land rice

Abstract: High nitrogen (N) rate often leads to low yield of rice due to lodging and mutual shading. This study was conducted to ascertain whether silicon (Si) could enhance yield response of rice to higher N rate by enhancing rigidity of plant parts and improving photosynthesis. The effects of Si and N on crop growth, photosynthesis, N use efficiencies and yield of rice were investigated during wet season (June to November) in sub-humid tropical region of India. An increasing trend in crop growth rate with Si at all le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…However, most studies related to Si-amendment sources application focused on soil chemical shifts instead of plant growth promotion, and nutrient uptake and imbalance. The application of various forms of Si (i.e., slag materials, silica powder, silicates, among others) could improve plant growth and development with greater nutrient uptake in different crops [ 16 , 19 , 20 , 21 ]. Haddad et al [ 22 ] indicated a beneficial effect of Si treatment in alleviating damage associated with nitrogen (N) deficiency in rapeseed ( Brassica napus L.).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most studies related to Si-amendment sources application focused on soil chemical shifts instead of plant growth promotion, and nutrient uptake and imbalance. The application of various forms of Si (i.e., slag materials, silica powder, silicates, among others) could improve plant growth and development with greater nutrient uptake in different crops [ 16 , 19 , 20 , 21 ]. Haddad et al [ 22 ] indicated a beneficial effect of Si treatment in alleviating damage associated with nitrogen (N) deficiency in rapeseed ( Brassica napus L.).…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [14] reported that Si content in Oxisols in the tropical zone can be less than 1% due to intense weathering processes. Highly weathered tropical and subtropical soils under continuous cropping systems are generally low in available Si content due to heavy desilication of primary silicate minerals, release and leaching of basic cations with decreased base saturation, and crop removal [3,7,15,16]. Therefore, the decrease in Si availability in tropical soils might have significant impacts on cropping systems if not properly managed.…”
Section: Introductionmentioning
confidence: 99%
“…Si provision improved the yield of rice by increasing the mobilization of photoassimilates and amino acids from vegetative tissues to grain and nitrogen use efficiency. It redirected the primary metabolism by acting as a signaling factor under unstressed conditions (Pang et al, 2019;Mohanty et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A strategy to mitigate nutritional disorders of N is to utilize silicon (Si), as it mitigates the symptoms of stress caused by N deficiency (Deus et al, 2020) and NH4+ toxicity (Gao et al., 2014). Furthermore, Si has beneficial uses such as increasing the efficiency of N utilization linked to an overall increase in chlorophyll abundance and photosynthesis (Mohanty et al., 2020). However, a more parsimonious explanation is that Si prevents or mitigates the strains imposed by stress, which is then reflected in a reduced induction of oxidative stress (Coskun et al., 2019).…”
Section: Introductionmentioning
confidence: 99%